The phantom of Manhattan - Forsyth, Frederick, 1938- (St. Martin's Press, 1999)
With the help of the woman who had originally freed him from torment, the Phantom of the Opera escapes by ship to America to begin a new and secret life that leads him to power and wealth, until a mysterious death-bed message transforms his life once again